Early Implanon Discontinuation and Associated Factors among Implanon User Women in Debre Tabor Town, Public Health Facilities, Northwest Ethiopia, 2016 - Melkamu Asaye, Mengstu; Syoum Nigussie, Tewodros; Mequannt Ambaw, Worku (International Journal of Reproductive Medicine, 2018)
Background. Implanon discontinuation closely related to higher rates of overall fertility rate, unwanted pregnancies, and induced abortion. This might have social and economic consequences. In Ethiopia the magnitude of early Implanon discontinuation and contributing factors is not well studied. Objective. To assess early Implanon discontinuation and associated factors among Implanon user women in Debre Tabor town, 2016. Methods. A facility based cross-sectional study was conducted from May 1 to August 2016 through face-to-face interview. A total of 449 Implanon user women were selected by systematic random sampling technique. Epi Info version 7 and SPSS version 20 were used for data entry and analysis, respectively. Factors associated with early Implanon discontinuation were analyzed using binary and multivariable logistic regression model. Variables with p value of <0.05 and 95% confidence interval were considered as statistically significant. Results. The overall proportion of early Implanon discontinuation among mothers was 65 % (95%, CI: 60.4%–69.5%). Having no children (AOR = 2.0, 95% CI = [1.3–4.5]), being not counseled for possible side effects (AOR = 1.50, 95% CI = [1.1–3.4]), having no appointment for follow-up (AOR = 2.6, 95% CI = [1.2–4.3]), and having developing side effects (AOR = 1.7, 95% CI = [1.5–4.4]) were found to be statistically significant factors associated with early Implanon discontinuation. Conclusion and Recommendation. Early Implanon discontinuation among mothers was found to be high. Hence, counseling about Implanon side effects and appointment for follow-up of Implanon users should be made to increase Implanon retention.